Penerapan Metode Harris Benedict Pada Media Informasi Kebutuhan Gizi Harian Berbasis Android - Muhammad Haris Qamaruzzaman; Sutami Sutami; Sam'ani Sam'ani; Irwan Budiman (STMIK Budi Darma, 2022)
Calculation of nutritional needs is a way to find out a person's nutritional needs, which is usually done by nutritionists before compiling a diet menu. One formula that is often used is the Harris Benedict formula. The problem of this research is how to make an application for calculating nutritional needs with the Harris Benedict formula based on android mobile. This application aims to assist nutritionists and ordinary users in calculating nutritional needs through the results of calculations and dietary advice provided. The methodology in this study uses research and development which includes observation/data collection, interviews and literature study. As for software development using the waterfall model development method (waterfall). The implementation is built with the Java programming language, IDE (Integrated Development Environment) with Eclipse applications, Software Development Kit (SDK) which includes API (Application Programming Interface) tools. Testing is done by black box testing to evaluate the external appearance (Interface) and application functionality. This research has succeeded in implementing the Harris Benedict formula in an Android mobile-based nutritional needs calculation application that provides output for weight categories, ideal body weight, and dietary advice. Other features include a list of food and household sized tools, and an application guide. The purpose of this study is to produce an application that helps users calculate nutritional needs faster than manual calculations with correct results such as manual calculations. From the results of testing the application in black box, the results are in line with expectations.